Yield and quality attributes of lettuce and spinach grown in different hydroponic systems - ACHARYA, SOMEN; KUMAR, KAUSHAL; SHARMA, NISHA; TIWARI, VIVEK KUMAR; CHAURASIA, O. P. (Journal of Soil and Water Conservation, 2022)
The present study evaluated the growth response, yield and nutritional quality of lettuce and spinach grown in different hydroponic systems viz. circulated nutrient film technique (NFT) system and noncirculated system and compares them with conventional open field condition. Lettuce and spinach both exhibited significant improvement in leaf area, fresh weight and yield in NFT system of hydroponics compared to open field condition. However, plant height, root length and number of leaves per plant did not differ significantly among the treatments. There was 169 and 107% higher lettuce yield in NFT and non-circulating system, respectively, whereas the corresponding increase in spinach was 190 and 124%. Significantly higher content of nitrate, phosphorus and sulphur was observed in hydroponically grown lettuce and spinach, especially in NFT system. Higher soluble sugar content in hydroponic spinach as well as in lettuce indicated better quality produce in hydroponic system which affects the sweetness and crispness of leafy vegetables. Overall, from the study it can be said that NFT system of hydroponics is performing better than other growing systems for rapid harvesting, higher productivity and quality produce of leafy vegetables. Since NFT system requires small space, this system may be promoted in urban areas of India as an alternative to conventional farming.